2018
DOI: 10.1186/s12915-018-0613-5
|View full text |Cite
|
Sign up to set email alerts
|

Two-component cyclase opsins of green algae are ATP-dependent and light-inhibited guanylyl cyclases

Abstract: BackgroundThe green algae Chlamydomonas reinhardtii and Volvox carteri are important models for studying light perception and response, expressing many different photoreceptors. More than 10 opsins were reported in C. reinhardtii, yet only two—the channelrhodopsins—were functionally characterized. Characterization of new opsins would help to understand the green algae photobiology and to develop new tools for optogenetics.ResultsHere we report the characterization of a novel opsin family from these green algae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(57 citation statements)
references
References 63 publications
0
44
0
Order By: Relevance
“…The LHCBM1 gene is a chlorophyll a / b binding protein in the light‐harvesting complex II. In previous RNA‐seq studies, the LHCBM1 promoter demonstrated strong expression and the expression levels were similar in both cell types (Klein et al , ; Tian et al , ). A 0.9 kb DNA fragment containing the LHCBM1 promoter region was introduced in front of the fused genes using Kpn I/ Apa I for babo1 / yfp and Xho I/ Xho I for cfp / tubB2 , resulting in the plasmids pBlue_LHCBM1_Babo1_YFP (Figure b) and pBlue_LHCBM1_CFP_TubB2 (Figure d).…”
Section: Methodsmentioning
confidence: 76%
See 4 more Smart Citations
“…The LHCBM1 gene is a chlorophyll a / b binding protein in the light‐harvesting complex II. In previous RNA‐seq studies, the LHCBM1 promoter demonstrated strong expression and the expression levels were similar in both cell types (Klein et al , ; Tian et al , ). A 0.9 kb DNA fragment containing the LHCBM1 promoter region was introduced in front of the fused genes using Kpn I/ Apa I for babo1 / yfp and Xho I/ Xho I for cfp / tubB2 , resulting in the plasmids pBlue_LHCBM1_Babo1_YFP (Figure b) and pBlue_LHCBM1_CFP_TubB2 (Figure d).…”
Section: Methodsmentioning
confidence: 76%
“…However, no transmembrane spanning segments have been identified and all of these programs predicted that Babo1 is not a transmembrane protein. Moreover, when yellow fluorescent protein (YFP)‐tagged Babo1 of C. reinhardtii (formerly Cop1/2) was expressed in Xenopus oocytes, YFP fluorescence was exclusively found in the soluble fraction of oocyte extracts but not in the membrane fraction (Tian et al , ). As a consequence of these results, Babo1 cannot be an opsin, which would necessarily require a transmembrane structure with generally seven transmembrane helices.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations